Research on combustion process of a free piston diesel linear generator. (1st January 2016) - Feng, Huihua; Guo, Chendong; Yuan, Chenheng; Guo, Yuyao; Zuo, Zhengxing; Roskilly, Anthony Paul; Jia, Boru
Highlights: We study the exothermic properties of the FPDLG during the combustion process. We compare the combustion of TRE with FPDLG, and reveal the heat releasing characteristics of FPDLG. We validate the model with test data from a running FPDLG prototype. Abstract: The piston motion of a free-piston diesel linear generator (FPDLG) is different from the traditional reciprocating engine (TRE). Here we focused on a numerical simulation for the research on the combustion process of an FPDLG by adopting coupled models of zero-dimensional dynamics and multi-dimensional computational fluid dynamics (CFD). Piston dynamics model and CFD model to simulate the combustion process were set up based on the calculated results of free-piston motion, which were validated with tested data from a running FPDLG prototype. According to the coupled parameters of these two models, we studied the exothermic properties of the FPDLG during the combustion process through iterative computation, and compared the simulation results of a TRE to a FPDLG with comparable and similar structural parameters. The results indicated that, combustion in the FPDLG lasted for a longer time compared with that in the TRE. While the heat release before top dead center (TDC), the isochoric heat release, and the heat release during the rapid combustion period were low, the post-combustion became more intense. Furthermore, the average temperature in the cylinder was generally lower, while became higher in the end of expansion stroke. In addition, the maximum combustion pressure was lower and lasted for a shorter time.